A Study Of The National Aftercare Programme. - Navaratnam, V.; Chee, Kim Loy; Foong Kin, Foong Kin; Wong, Wai Ling; Chiang, Pik Har (Pusat Penyelidikan Dadah Kebangsaan, Universiti Sains Malaysia, 1992)
This study of the Aftercare Programme is a follow-up of an earlier study of official treatment and rehabilitation programmes for institutionalised drug dependents. The aims of this investigation were to provide an understanding of the aftercare programme and its relation to overall treatment and its rehabilitation efforts; to provide a description of the programme delivery process and analysis of the organizational aspects of the programme as perceived by programme officers.